Diakoptic Method as a Generalized Form of the Thevenin's Theorem - Matoušek, David; Brtník, Bohumil (IEEE (Institute of Electrical and Electronics Engineers), 2022)
This paper deals with the composition of a circuit matrix using the diakoptic method. The diakoptic method is a generalization of Thevenin's theorem. The diakoptic method allows solving complex electrical and electronic circuits. This method divides a complex electrical circuit into simpler circuits. The description of each of these circuits executes by the same or different method. For example, we can describe the first part of a circuit (with current sources) by the node voltage method. After then, we describe the second part of a circuit (with switched capacitors) by the nodal charge equations method, etc.
Diakoptická metoda jako zobecněná forma Theveninova teorému
Keywords: Thevenin's theorem; current source; voltage source; diakoptic method; matrix description; incidence matrix; Theveninův teorem; zdroj proudu; zdroj napětí; diakoptická metoda; maticový popis; incidienční matice